Growth of Purple Sweet Potato (Ipomea batatas L.) Majalengka Local Cultivar As Response of Organic Fertilizer with Different Time Application - Marwah Zulkarnain, Annisa
Sweet potato has been a staple food for Indonesia, which usually consumed as processed food or directly eaten. Nowadays, sweet potato species are diverse since it was domesticated into the country. Purple sweet potato (Ipomea batatas L.) is one of the new rising healthy food known for its nutritional value and bioactive compound. Availability of purple sweet potato still limited because the productivity is low compared to other varieties of sweet potato. The aim of this research is to discover the best treatments to growth of purple sweet potato (Vine length and its increase, shoot root ratio for vegetative and generative state, amount of primary brancher). Treatments used were combination of organic fertilizer (goat manures fertilizer, leaves compost, bokashi, and vermicompost) and time of aplication (day of planting, 30 days and 15 days in prior of planting). Total of 12 treatments with three replication conducted on randomized block design with a 2 factorial. Analysis of Variance (ANOVA) on 5% level intended to test treatment effect, meanwhile difference between mean values based on LSD 5% and DMRT 5%. Vine lengths trends shown continuous growth. Meanwhile, there is no interaction between two factor for increase of length, but treatments of fertilizer application with 30 days prior of planting significant within the same factor (1,86). Shoot root ratio for vegetative state shown the significant combination of vermicompost application with 30 days prior of planting (26,61). Meanwhile, shoot root ratio for generative state neither shown the significant combination between two factor nor the significance between data within the same factors. Amount of branches neither shown the significant combination between two factor nor the significance overall.